Supernatural religion and the problem of providence - Drum, Peter (Sophia, 2003)
There is a prima facie case of unfairness against God unless Self-revelation is given by the deity to all people. The possible replies that God's Self-revelation has always and everywhere been available to everyone through many religions; or that special knowledge of God is a matter of divine gratuity; or that more is expected of those who receive such enlightenment; or that it comes as a moral reward; are found to be wanting. Nevertheless, provided there remains an argument for selective divine Self-revelation in terms of spiritual readiness, the case against God remains unproven.